Role of depression and impulsivity as determinants of suicidal ideation among students in Ibadan, Nigeria (2017)
This study investigated the relationship between the risk factors of depression and impulsivity, and suicidal ideation among students of University of Ibadan. It adopted a cross-sectional survey research design and used questionnaire for data collection. Three scales were used in eliciting information from the students. Independent T-test Analysis was used in analyzing the data. P<. .001 level of confidence was considered significant. Two hypotheses were formulated and analyzed using independent t-test. The results show that high depressive and impulsive students have a greater likelihood of engaging in suicidal ideation than low depressive and impulsive ones (t - -5.694, df = 402, p< 0.001) and (t = -5.207, df = 402, p< 0.001). Consequently, students who are depressed as well as those who are impulsive must be closely monitored and assisted since they are at a higher risk of engaging in suicidal ideation than those who are not.